PERSEPSI PENYULUH DI KABUPATEN SUKOHARJO TERHADAP PERAN FUNGSIONAL ANGGOTA KELOMPOK - Dwiningtyas Padmaningrum (AGRITEXTS: Journal of Agricultural Extension, 2010)
Coordinating the actions of two or more individuals toward the achievement of a common goal is a problem for any organizational unit, included extension organization. These activities can be supported by communication of an informal or formal group, where the extension workers can respond to the functional role through their perception. Role is viewed as an individual’s conception in relation to their involvement in their groups. An understanding of the nature of roles and their impact is fundamental to the study of extension organizations. The research aims to study the perception of extension workers for their functional roles in groups. The location of research was Subdistrict : Mojolaban, Nguler and Polokarto, Regency of Sukoharjo. The method used in this research was analytical descriptive with survey technique. This research was analytical descriptive with survey technique. This research showed that the extension workers have a positive perception of their functional roles in groups. This positive perception indicates high level of involvement by individuals in group. In other word, such group supports performance of the extension organization ultimately.